Local Identity Studies of Gender Diversity and Sexual Orientation in ELT - Harold Castañeda-Peña (Asociación Colombiana de Profesores de Ingles, 2021)
While it is true that identity studies on the intersection between gender and sexual orientations with language teaching and learning are not new in the local context, the systematization of these studies as a body of knowledge is scarce. This article presents, first of all, a systematization of reference frameworks for this type of studies in historical perspective. Secondly, it presents a reflection on the collective achievements in this field of study. Finally, the article concludes with a brief reflection on potential actions at the research and pedagogical levels.